School Culture in Fostering Teachers’ Work Motivation - Imawati; Maryani, Ika; Zuhaery, Muhammad (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
School culture is crucial in creating a supportive work environment, which directly affects teacher motivation. Teacher motivation, as a key element in the education system, has a significant impact on the effectiveness of teaching and the quality of student learning outcomes. This study analyzes how indicators of organizational culture in schools, such as innovation, attention to detail, outcome orientation, individual orientation, and team orientation, affect teacher motivation. Using a qualitative approach through case studies, data were collected through semi-structured interviews and focus group discussions. The results showed that a culture that encourages innovation and measured risk-taking has a positive impact on teacher motivation. A culture that emphasizes attention to detail encourages a focus on teaching quality. In addition, a result-oriented culture motivates teachers by aligning their efforts with clear achievement goals. The study also revealed that a culture that supports individual development and professional growth significantly increases teacher motivation. Another important factor is effective leadership, which plays a vital role in fostering a positive and collaborative work atmosphere.